2021
DOI: 10.1371/journal.pntd.0009033
|View full text |Cite
|
Sign up to set email alerts
|

Variable bites and dynamic populations; new insights in Leishmania transmission

Abstract: Leishmaniasis is a neglected tropical disease which kills an estimated 50,000 people each year, with its deadly impact confined mainly to lower to middle income countries. Leishmania parasites are transmitted to human hosts by sand fly vectors during blood feeding. Recent experimental work shows that transmission is modulated by the patchy landscape of infection in the host’s skin, and the parasite population dynamics within the vector. Here we assimilate these new findings into a simple probabilistic model fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This is in agreement with [122], although slight reduction of sand fly prevalence was observed by Picado et al [45]. Fourth, we also do not consider increased mortality of infected sand flies [110,123]. To incorporate any of these last two improvements, one would have to consider m F ¼ m F (p) for an appropriate increasing function m F (p).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This is in agreement with [122], although slight reduction of sand fly prevalence was observed by Picado et al [45]. Fourth, we also do not consider increased mortality of infected sand flies [110,123]. To incorporate any of these last two improvements, one would have to consider m F ¼ m F (p) for an appropriate increasing function m F (p).…”
Section: Discussionmentioning
confidence: 56%
“…[45]. Fourth, we also do not consider increased mortality of infected sand flies [110,123]. To incorporate any of these last two improvements, one would have to consider μnormalF=μnormalFfalse(pfalse) for an appropriate increasing function μnormalFfalse(pfalse).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of multiple blood meals on sand fly infections under these conditions needs to be evaluated since experimentally infected sand flies that were blood-fed twice produced homogeneous infections that were less variable compared with those that were fed only once [29]. In fact, a probabilistic model for disease transmission incorporating parasite patchiness and multiple blood meals showed that the former is less important for successful transmission by longer-lived sand flies that take multiple blood meals [39]. Then, for a successful transmission event to occur, or to increase the frequency of successful transmission events [29,39], a subsequent blood meal becomes a critical part of the parasite's life cycle in nature.…”
Section: Trends Trends In In Parasitology Parasitologymentioning
confidence: 99%
“…In fact, a probabilistic model for disease transmission incorporating parasite patchiness and multiple blood meals showed that the former is less important for successful transmission by longer-lived sand flies that take multiple blood meals [39]. Then, for a successful transmission event to occur, or to increase the frequency of successful transmission events [29,39], a subsequent blood meal becomes a critical part of the parasite's life cycle in nature. This becomes even more relevant in natural transmission scenarios considering the low Leishmania infection rates observed in field vector populations [40][41][42].…”
Section: Trends Trends In In Parasitology Parasitologymentioning
confidence: 99%